Fabricação de queijo frescal incorporado com extrato de própolis e sua influência na aceitação sensorial e nas propriedades qualitativas - Mendonça, Lidiane Pinto de (Universidade Federal Rural do Semi-Árido, 2020)
The fresh cheese is classified as a high moisture and high nutrient rich food. As it is one of the products most susceptible to deterioration, it lacks technologies that favor the increase in useful life. Propolis is a natural product produced by Africanized bees, which due to its biological compounds has antimicrobial and antifungal action. Thus, the aim was to manufacture a fresh type cheese incorporated with propolis extract and to verify its influence on sensory acceptance and qualitative properties. Initially, six samples of fresh cheese were produced, four of which were incorporated with 10% and 15% propolis extract and two without the addition of propolis (control). The samples were stored in a vacuum and normal atmosphere, and placed in microbiological analysis (analysis of molds and yeasts and mesophilic bacteria), physical-chemical (pH, acidity, loss of mass, moisture and color), sensory and visual aspects. The treated cheeses showed no statistical differences in relation to sensory analysis. The addition of 15% green propolis extract controlled the contamination by fungi and mesophilic bacteria in the analyzed samples. Over nine days of refrigerated storage, the physical-chemical parameters of the treated samples remained stable, not statistically differing by the T test. It was found that in visual aspects the addition of propolis extract did not interfere negatively when analyzed with the naked eye. Therefore, it was concluded that the addition of green propolis extract in fresh cheeses can be promising for conservation as a substitute for synthetic preservatives.
Keywords: Produtos lácteos; Análise de alimentos; Qualidade de produtos de origem animal; Dairy products; Food analysis; Quality of products of animal origin; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL